Obstacles to the implementation of professional learning communities among UNRWA school teachers in the Jerusalem; Jericho Area from teachers’ perspective - Marbou, Sahar Said (Journal of Educational and Psychological Sciences, 2024)
The study is mainly established to highlight some obstacles facing the implementation of professional learning communities among UNRWA teachers in the Jerusalem; Jericho area from their perspective. To achieve this goal, the researcher followed the descriptive analytical approach, using a questionnaire of (36) statements, representing three different areas of obstacles hindering the implementation of professional learning communities. The questionnaire was distributed to (100) male and female teachers randomly. The results of the study have shown that the obstacles were of an overall average of (3.15), with a (medium) degree؛ where obstacles associated with school environment had the highest average of (3.47) large degree, followed by the obstacles associated with teachers with an average of (3.04), then obstacles related to school administration with an average of (2.92), both with a moderate degree. Additionally, the results showed statistically based differences at the level (0.05 ≥ α) about obstacles related to gender variable, in favor of males, academic qualification, in favor of MA holders, yet no differences related to years of service in all fields. In light of the results, the researcher recommended an urgent need to train and qualify teachers to implement professional learning communities, stressing the need of administration collaboration to activate such communities. Upon the given results, it is worth considering some issues that have emerged and conducting more studies in this field ahead.
Keywords: obstacles; professional learning communities; UNRWA; Jerusalem